2003
DOI: 10.1063/1.1564298
|View full text |Cite
|
Sign up to set email alerts
|

Ge-fraction-dependent metal-induced lateral crystallization of amorphous-Si1−xGex (0≦x≦1) on SiO2

Abstract: Metal-induced low-temperature (≦550 °C) crystallization of amorphous-Si1−xGex (0≦x≦1) on SiO2 has been investigated. In the case of low Ge fraction (0≦x≦0.2), Ge-doping enhanced plane growth was observed. This achieved strain-free poly-Si0.8Ge0.2 with large grains (18 μm). On the other hand, dendrite growth became dominant in the case of intermediate Ge fractions (0.4≦x≦0.6). By optimizing the growth conditions (x: 0.4, annealing: 450 °C, 20 h), very sharp needle-like crystal regions (width: 0.05 μm, length: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…8 However, the velocity of MILC is so low that a long annealing time ͑ϳ20 h͒ is necessary to obtain large poly-Si areas ͑ϳ10 m͒ at 550°C. 9 We have studied the influences of Ge doping in a-Si on the enhancement of MILC, and found that the velocity could be enhanced by 80% with increasing Ge fraction from 0 to 20%. However, the regrown regions showed dendritelike morphology.…”
mentioning
confidence: 98%
“…8 However, the velocity of MILC is so low that a long annealing time ͑ϳ20 h͒ is necessary to obtain large poly-Si areas ͑ϳ10 m͒ at 550°C. 9 We have studied the influences of Ge doping in a-Si on the enhancement of MILC, and found that the velocity could be enhanced by 80% with increasing Ge fraction from 0 to 20%. However, the regrown regions showed dendritelike morphology.…”
mentioning
confidence: 98%
“…The situation is even worse for SiGe-alloys. To the best of our knowledge, so far only one report dealing with the influence of Ge content on the lateral crystallization morphology for Niinduced crystallization of Si 1-x Ge x has been published [23]. However, this approach is not a suitable option for solar cell applications, since a high concentration of Ni remains in the recrystallized SiGe layers, and Ni ions in Si are very efficient recombination centers.…”
Section: Aluminium-induced Crystallization Of Sige Filmsmentioning
confidence: 97%
“…Consequently, such a silicide acts as a seed for solid-phase epitaxial growth. This metal-induced lateral crystallization (MILC) has realized the growth of poly-Si with large grains ($10 lm) on insulating films, and has been investigated to apply to SiGe [12][13][14]. These grains are, however, composed of many small sub-grains resulting from a number of uncontrolled nucleations and the film contains large amounts of Ni.…”
Section: Introductionmentioning
confidence: 98%